Strange encounters: embodied others in post-coloniality - Ahmed, Sara (Transformations : thinking through feminism, 2000)
"Examining the relationship between strangers, embodiment and community, Strange Encounters challenges the assumptions that the stranger is simply anybody we do not recognize and instead proposes that he or she is socially constructed as somebody we already know. Using feminist and postcolonial theory this book examines the impact of multiculturalism and globalization on embodiment and community whilst considering the ethical and political implication of its critique for post-colonial feminism. A diverse range of texts are analyzed which produce the figure of 'the stranger', showing that it has alternatively been expelled as the origin of danger - such as in neighbourhood watch, or celebrated as the origin of difference - as in multiculturalism. The author argues that both of these standpoints are problematic as they involve 'stranger fetishism'; they assume that the stranger 'has a life of its own'". -- Site de l'éditeur.
Keywords: approches et analyses; corps; cours; discipline; féminisme décolonial; histoire et politique; lit4700; philosophie; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; études culturelles

Mort ou fif: la face cachée du suicide chez les garçons - Dorais, Michel; Lajeunesse, Simon Louis (Des hommes et des femmes en changement, 2000)
A partir de témoignages et récits de vie, cet ouvrage met en lumière la relation entre le mépris et l'ostracisme dont sont victimes les adolescents homosexuels ou considérés comme tels et leur haut taux de suicide. Une version revue et corrigée d'un document publié par le Centre de recherche sur les services communautaires de l'Université Laval (octobre 2000).
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Invisible lives the erasure of transsexual and transgendered people - Namaste, Viviane K. (University of Chicago Press, 2000)
Invisible Lives est la première étude scientifique sur les personnes transgenres – travestis, drag queens et transsexuels – et sur leur vie quotidienne. À travers une étude théorique et empirique combinée, Viviane K. Namaste soutient que les personnes transgenres ne sont pas tant produites par la médecine ou la psychiatrie qu'elles sont effacées ., ou rendu invisible, dans une variété de contextes institutionnels et culturels. Namaste commence son travail en analysant deux perspectives théoriques sur les personnes transgenres - la théorie queer et les sciences sociales - montrant comment aucune d'entre elles n'a abordé de manière adéquate les problèmes les plus pertinents pour le changement de sexe : tout, de l'emploi aux soins de santé en passant par les papiers d'identité. Namaste examine ensuite certaines des inscriptions rhétoriques et sémiotiques des figures transgenres dans la culture, y compris des études sur les premières sous-cultures punk et glam rock, pour illustrer comment l'effacement des personnes transgenres est organisé dans différents sites culturels. Invisible Lives se termine par de nouvelles recherches sur certaines des préoccupations quotidiennes des personnes transgenres, proposant des études de cas sur la violence, les soins de santé, les cliniques d'identité de genre et la loi.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discours dominant; fem1000; identités LGBTQIA2+; personnes trans*; premier cycle; queer; santé; sexualité; systèmes d'oppressions; thématiques; théories féministes; vie quotidienne; violences; études culturelles

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme